Risk management and coping strategies: Climate change and agriculture in the Philippines - Majah-Leah V. Ravago; James Alan Roumasset; Karl Jandoc (University of the Philippines, School of Economics (UPSE), 2015)
We provide an initial framework regarding priorities for government programs to reduce the natural-disaster vulnerability of farm households in the Philippines. We begin with the likelihood that climate change will increase the probability of flooding, since rainfall is expected to both increase and be more concentrated (more storms). We then turn to a conceptual framework for understanding resilience at the household level and evidence from the PCED Social Protection Survey about coping strategies of farm households. The framework can be used to shed light on pros and cons of alternative public policies to reduce household vulnerability, including the role of discounting. In particular, we highlight the limited coping tools available to low-income households. This helps to strengthen the case for preventative polices that lower the probability and/or severity of damages. The inability of poor households to cope with increased exposure to risks, however, does not necessarily imply that social insurance programs should be expanded. Inasmuch as disaster risk management policies at the national level are typically without coherent foundations, we provide tentative indications of how the farm level risk-management framework can be expanded to the national level.
Keywords: Q12; Q54; D81; I38; 330; Farm-household risk management; natural disaster; shock; coping